Molecular Analysis of Goodpasture’s Disease Following Hematopoietic Stem Cell Transplant in a Pediatric Patient, Recalls the Conformeropathy of Wild-Type Anti-GBM Disease - Gray, Paul E.; McCarthy, Hugh; Siggs, Owen M.; Saleem, Moin A.; O' Brien, Tracy; Frith, Katie; Ziegler, John B.; Kitching, A. Richard; Fogo, Agnes B.; Hudson, Billy G.; Pedchenko, Vadim (Frontiers in Immunology, 2019)
Goodpasture’s disease (GP) is mediated by autoantibodies that bind the glomerular and alveolar basement membrane, causing rapidly progressive glomerulonephritis with or without pulmonary hemorrhage. The autoantibodies bind neoepitopes formed upon disruption of the quaternary structure of α345NC1 hexamer, a critical structural domain of α345 collagen IV scaffolds. Hexamer disruption leads to a conformational change that transitions α3 and α5NC1 subunits into immunogens, however, the trigger remains unknown. This contrasts with another anti-GBM disease, Alports’ post-transplant nephritis (APTN), where the pathogenic alloantibody binds directly to native NC1 hexamer. The current report includes the first in depth study of allo-incompatability and antigenic specificity in anti-GBM disease occurring after allogeneic haematopoietic stem cell transplant (HSCT). No polymorphic genetic differences were identified between donor and recipient collagen IV genes which would be predicted to provide a target for antibody binding, meaning this is a true post-transplant autoimmune rather than alloimmune phenomenon. Furthermore, autoantibody binding to native α345NC1 hexamer was minimal, increasing greatly upon dissociation of the native hexamer, resembling wild-type GP diseases and marking this as the first example of a post-HSCT conformopathy. The anti-GBM antibodies were found to be directed predominantly against the EA epitope of the α3NC1 monomer of collagen IV and developed rapidly in patient serum reaching peak levels within 5 weeks. Both patient and donor possessed the Goodpasture’s susceptibility HLA-allele DRB1*1501. This is the first report of anti-GBM disease occurring post-HSCT where the pathogenesis has been studied extensively. The specificity and binding properties of the antibodies along with sequencing results, indicate that this is a post-transplant autoimmune rather than alloimmune phenomenon, and that this disease is a conformopathy similar to wild-type Goodpasture’s.